The Effect of The Addition of Seaweed Charcoal (Sargasum sp.) With Pure Graphite on The Absorptive Properties of Graphene Oxide Syntheses Using the Hummer Modification Method - Dicko Maulana Syahdan; - Ramli; Rahmat Hidayat; Yenni Darvina (Department of Physics – Universitas Negeri Padang UNP, 2023)
Graphene Oxide or Graphene Oxide (GO) Is a graphite oxide in the form of a monolayer obtained from exfoliating graphite oxide into sheets through a sonication or stirring process. In this study, the material used was a mixture of pure graphite and seaweed (Sargasum sp). Seaweed (Sargasum sp) is used as a mixture of pure graphite because the carbon content in seaweed (Sargasum sp) is good enough to reduce the use of pure graphite as the main ingredient in making graphene oxide. There are are 4 variations of composition with the aim of seeing the best results from these five compositions, namely the composition between Graphite and Sargassum sp, namely 70%: 30%, 60% ; 40%, and 50% : 50%. The research results obtained showed that graphene oxide had been successfully synthesized from the addition of seaweed charcoal because of some of the typical properties of graphene oxide. By X-ray diffractogram at an angle of 2, it was found to contain C-O, C=O, C=C, and O-H functional groups. In the VNA test, it obtained high reflection loss and adsorption coefficient values in a mixture of 50% pure graphite: 50% seaweed with a reflection loss value of -7.40 dB and an adsorption coefficient of 0.57342